Comparison Level of Vitamin D Based on Body Mass Index Healthy Individual in Central Laboratory RSUP Dr. M.Djamil Padang - Efrida Efrida (Majalah Kedokteran Andalas, 2022)
Vitamin D deficiency is associated with various pathological condition like bone diseases, autoimmune diseases, metabolic syndrome, malignancies and infections. Obesity is a risk factor for vitamin D deficiency even though there is no evidence of a suitable causal relationship. This study aimed to compare the levels of 25(OH)D, based on body mass index (BMI). Observational study with cross-sectional design on subjects in Central Laboratory RSUP dr. M. Djamil. Subjects were divided into 2 groups based on BMI for Asia Pacific, namely normal body weight (BMI 18.5-22.9 kg/m2) and excess body weight (BMI ≥23 kg/m2) that met the inclusion and exclusion criteria. Serum 25(OH)D were examined using the immunoassay method. For the hypothesis test a bivariate comparative test is carried out using unpaired T test (numerical data) and Chi-Square test (categorical data). Statistical significancy is if  p < 0.05.  The mean (SD) 25(OH)D levels in normal and overweight subjects were 15.11 (5.46) ng/mL and 15.59 (5.85) ng/mL, p> 0.05, respectively.